Pengaruh Minat Belajar dan Kualitas Pertemanan Sebaya Terhadap Konsep diri Remaja SMA/SMK Sederajat di Kecamatan Pondok Kelapa Kabupaten Bengkulu Tengah - Mahardilla, Devita; Saputri, Anissa; Puspita Sari, wiwied; Badriyah, Lailatul (Yayasan Darussalam Bengkulu, 2023)
This article aims to examine how much influence interest in learning and the quality of peer friendship on self-concept in high school / vocational students of the same level in Pondok Kelapa District, Central Bengkulu Regency. The population in this study was adolescents in SMA/SMK sub-district of Pondok Kelapa, Central Bengkulu. This research uses a quantitative approach with a descriptive type of research. The sample in this study was 130 high school / vocational students as respondents. The type of data collection used in this study is a Likert scale questionnaire or using questionnaire survey techniques by distributing targets to respondents, as many as 30 statements consisting of 10 statements from self-concept indicators, 10 statements from learning minar indicators and 10 statements from peer friendship quality indicators. The analysis techniques used are Data Normality Test, Reality Test, Correlations Test, Descriptive Statistics Test, Model Summary Test, and Anova Test thus testing is carried out testing is carried out using. Based on the results of research and discussion, it can be concluded that the interest in learning and the quality of peer friendship affect the self-concept of high school / vocational students in Pondok Kelapa district, Central Bengkulu district. The influence of learning interest and friendship quality on self-concept reached 16.7%, while the remaining 83.3% was influenced by other variables.